Konsep Khamar dan Narkotika dalam al-Qurâ€™an dan UU - Ashar, Ashar (FENOMENA, 2015)
In this modern era, Khamar (liquor) is more identical and better known by the name of drugs (narcotics, psychotropic, and other dangerous drugs). Drugs are forbidden to consume for human. Narcotics and psychotropic are cited in Law Number 22 of 1997 where both are Khamars. In Law Number 5 of 1997, psychotropic is a drug or a substance, natural or synthetic, both are not narcotics which have psychoactive effect through central nervous system that causes typically changes in mental activity and behavior. This study is descriptive qualitative. Research on Law, descriptive is to show or describe individual accurately, condition, symptom or a particular group, and to determine the spread of a phenomenon. It is stated that someone is a drunk of Khamar and gets a Had punishment when she or he is tried and true or proved by his or her self-testimony or two witnesses. Law number 35 of 2009 about narcotics classifies a criminal of drug abuse into two types; the criminal as a drugs user is cited 116, 121 and 127 articles and the criminal is not as a drug user is cited in 112, 113, 114, and 129 articles. There are two types of drugs users, for himself and drug dealer (cited in 116 and 121 articles). The drugs users without any doctorâ€™s supervision, they should be rehabilitated when they are addicted. But for the criminal as drugs not-user, is classified into four; owner (cited in 111 and 112 articles), producer (cited in 113 article), carrier (cited in 114 and 119 articles), drugs dealer (cited in 129 article). So that, base-foundation of Islamic Laws is based on â€œbenefitted, resisted damage and danger.â€ The importance of Islamic Law to be built based on resisted damage and danger is to prevent and prohibit all kinds of substances that endanger.